Digital Papyrology I : Methods, Tools and Trends - Reggiani, Nicola (Berlin ; Boston : De Gruyter, 2017)
Since the very beginnings of the digital humanities, Papyrology has been in the vanguard of the application of information technologies to its own scientific purposes, for both theoretical and practical reasons (the strong awareness towards the problems of human memory and the material ways of preserving it; the need to work with a multifarious and overwhelming amount of different data). After more than thirty years of development, we have now at our disposal the most advanced tools to make papyrological studies more and more effective, and even to create a new conception of "papyrology" and a new model of "edition" of the ancient documents. At this turining point, it is important to build an epistemological framework including all the different expressions of Digital Papyrology, to trace a historical sketch setting the background of the contemporary tools, and to provide a clear overview of the current theoretical and technological trends, so that all the possibilities currently available can be exploited following uniform pathways. The volume represents an innovative attempt to deal with such topics, usually relegated into very quick and general treatments within journal articles or papyrological handbooks.
Frontmatter -- Acknowledgment -- Table of Contents -- 1. Tablets of the Mind (An Introduction) -- 2. Digital Bibliographies and Bibliographical Standards -- 3. Cataloguing Metadata -- 4. Indexing Words -- 5. Virtual Papyrology -- 6. Papyrological Mass Media -- 7. New Trends in Digital Papyrology -- 8. From Textual Databases to Digital Scholarship -- 9. The Shape of Things to Come (Not A Conclusion) -- Appendix 1. Clarysse's software -- Appendix 2. The DIGMEDTEXT Project -- Bibliography -- Indices
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 15. Jun 2019)
Keywords: Digital humanities; Manuscripts, Classical (Papyri) -- Data processing; Manuscripts, Classical (Papyri) -- Technological innovations; Manuscripts, Classical (Papyri).; Manuscripts, Greek (Papyri) -- Data processing; Manuscripts, Greek (Papyri) -- Technological innovations; Manuscripts, Greek (Papyri).; Manuscripts, Latin (Papyri) -- Data processing; Manuscripts, Latin (Papyri) -- Technological innovations; Manuscripts, Latin (Papyri).; Digital papyrology; Edition /digital.; Papyrologie /digitale Edition; digital classics; digital edition of ancient documents; digital humanities; Papyrologie; Digital Humanities